Chemodiversity of Ursane‐ and Oleanane‐Type Triterpenes in Amazonian Burseraceae Oleoresins. Issue 6 (18th June 2013) - Rüdiger, André L.; Veiga‐Junior, Valdir F.
Abstract The oleoresins exuded from species of the Burseraceae family present high potential due to their biological and pharmacological properties. The evaluation of the chemodiversity of the oleoresins of 23 Amazonian species of Burseraceae provided a profile of the principal constituents, viz., the ursane‐type triterpenes α‐amyrin (1), α‐amyrenone (3), and brein (5) and the oleanane‐type triterpenes β‐amyrin (2), β‐amyrenone (4), and maniladiol (6), and allowed to determine which of these species have the highest biotechnological potential and which ones are rich in other, potentially new, triterpenes or volatile compounds of interest for the cosmetics industry. The oleoresin compositions obtained by GC‐FID and GC/MS analyses were submitted to principal component analysis (PCA) and hierarchical clustering on principal components (HCPC), which divided the 23 samples in five clusters. Protium giganteum and Trattinnickia peruviana, constituting the first cluster, presented high oleoresin contents of 3 and 4 (28.8 and 16.3% on average, resp.). The seven species of Burseraceae composing the second cluster were potential producers of new triterpenes and volatile compounds. Dacryodes hopkinsii and five Protium species (third cluster) presented average contents for all the triterpenes analyzed. The highest contents of 5 and 6 (averages of 3.9 and 5.4%, resp.) were observed in P. heptaphyllum ssp. ullei and T. glaziovii (fourth cluster). Finally, the six Protium species forming the fifth cluster showed high contents of 1 and 2 (48.0 and 19.9% on average, resp.). Moreover, this study allowed the description of the triterpene composition of 13 not previously investigated species.